“Dosis de microorganismos beneficos, en una dosis de materia orgánica (pollaza), en el cultivo de cebolla china (allium fistulosum ) Var. Roja chiclayana, en la provincia de Lamas-San Martín - Robledo Alverca, María Olivia (2014)
This research was conducted at the farm "The Pacific" located in the district and province of Lamas, San Martin department, with geographical location of 76 º 30 '45 'W, 06 º 20' 15" latitude msnmm south and 835, with the objective of evaluating the quality of crop yield and Chinese onion (Allium fistolosum) chiclayana red range, in a dose with 20 t.ha-1 pollaza, compared with 4 doses of biological organisms (EM) applied to the soil. Also determine the cost of production for each treatment in a cost / benefit analysis. The doses studied Biological Microorganisms: 3 l.ha-1 (T1), 6 l.ha-1 (T2), 9 l.ha-1 (T3}, 12 l.ha-1 (T4) and no application (T5), respectively for each treatment, the effective microorganisms were applied 15 days before sowing, at the time of incorporating pollaza, then at the time of sowing and 15 days after planting. The assessments were made under a Design Randomized Complete Block with five treatments and four replications. The best results obtained with the application of MB for ali evaluated variables was undoubtedly the T4, of (12 l.ha-1 MB) reported the highest average yields with ; 91, 112.5 kg ha-1, 182.23 g weight of the plant, 42.48 cm of plant length, 1.57 cm in diameter and 1.51 cm bulb diameter of the base of the plant statistically averages beating achieved by other treatments. Keywords: Biological microorganisms, pollaza